Strategi pemberdayaan masyarakat dalam penanggulangan stunting: pemahaman, pencegahan, dan intervensi - Widhi, Bidari Andaru; Abdussamad, Zainudin; Muhid, Abdul; Miswaty, Titik Ceriyani; Yuliana, Ika; Patty, Elyakim Nova Supriyedi; Iriyani, Sri Astuti; Marlina, Marlina (INDRA: Jurnal Pengabdian kepada Masyarakat, 2025)
This community service discusses stunting, a problem of stunted child growth due to chronic malnutrition, especially in the West Nusa Tenggara region of Indonesia. Stunting causes impaired growth in children, with boys growing much less than they should. This condition is often caused by a lack of nutritional knowledge among pregnant women and children, as well as an unbalanced diet. The impact of stunting includes physical and cognitive impairment, increased risk of chronic disease, and lower adult productivity. Stunting prevention requires a holistic approach involving nutrition, health, sanitation and education, as well as active participation from the government, community and family. An intervention program was implemented in Bayan, North Lombok, involving participatory discussions with various community members to improve understanding and prevention of stunting. The PAR method was used in the implementation of the activities, which involved initial mapping, implementation, and evaluation. The results showed an increase in the community's understanding of stunting and its prevention measures. The program highlights the importance of community empowerment in stunting prevention to improve children's quality of life.